Pola Komunikasi Guru dan Siswa dalam Pembinaan Akhlak di Sekolah Islam - Izzudin Hitimala; Ahmad Faisal (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the communication patterns between teachers and students in fostering moral development within Islamic schools through a systematic literature review approach. The research focuses on Islamic educational communication as a pedagogical and moral instrument in shaping students’ character formation. Data were obtained from academic journals, scholarly books, and scientific publications discussing interpersonal communication, persuasive communication, moral habituation, religious school culture, and character education within Islamic educational contexts. The findings indicate that interpersonal communication contributes to pedagogical trust and normative interaction between teachers and students, while persuasive and exemplary communication strengthens moral legitimacy and value internalization among learners. Religious habituation embedded in school culture reinforces ethical discipline and spiritual awareness among students. The study also reveals that communication effectiveness is influenced by family involvement, digital media exposure, heterogeneous student backgrounds, and institutional religious culture. This research contributes to the development of Islamic educational communication theory by positioning moral communication as an integrative process involving pedagogical, cultural, and social dimensions.